Pendidikan Pesisir Selat Malaka: Analisis Nilai, Strategi, dan Relevansi dalam Pembangunan Karakter Masyarakat Pesisir - Fahrina Yustiasari Liriwati; Zulhimma Zulhimma; Ali Pirdaus (Lembaga Pengembangan Kinerja Dosen, 2024)
This study is a library research that aims to analyze the concept and relevance of coastal education in the Straits of Malacca in shaping character and improving the welfare of maritime communities. The study reviews a wide range of literature, including scientific journals, books, and policy documents related to character education, Malay local wisdom, and environmental education in coastal areas. The findings indicate that education in the coastal region of the Straits of Malacca serves not only as a means of knowledge transmission but also as a medium for internalizing the cultural and moral values of the Malay maritime community—values characterized by religiosity, independence, and environmental awareness. The ideal form of coastal education is an integrative model that combines Islamic character values, local wisdom, and ecological consciousness within a contextual learning system that reflects the realities of maritime life. The study concludes that strengthening character education based on coastal culture can serve as an effective strategy for creating resilient, competitive, and sustainable coastal societies amid global social and ecological change.